STRATEGI PENGEMBANGAN PARIWISATA DI KABUPATEN WONOGIRI - Andriyani Perwita Kusuma; Nina Widowati; Susi Sulandari (Journal of Public Policy and Management Review, 2013)
This research aims to whather the current strategy is not effective or not. Research design used is descriptive qualitative reesearch with descriptive qualitati method. Informants in this study is the head of the field of tourism and marketing cation of Disbudparpora Wonogiri disctrict, the head of government of Setda Wonogiri district. Technique use is technique purposive sampling and random.Of the results showed the condition of the district tourism Wonogiri not good. SWOT analysis, resulting strategy is promoting of the potential that exist in the district Wonogiri order to attract investors to invest in the tourism sector with the aim of improving the walfare of soiciety.Conclusion of this study is to function as a SWOT analisys of strategy formulation. Tourism development strategy Wonogiri district a affected by vision and mission, human resources, budget, facilities and infrastructure, commitment stakeholder, economic factor, social and cultural, regulatory, role pokdarwis. To improve and develop tourism in the disctrict Wonogiri, authors suggest to Disbudparpora disctric Wonogiri to improve the quality of human resources, collaborate with stakeholders, creating distinctive new food product.